2021
DOI: 10.1111/nuf.12583
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of critical care nurses fighting against COVID‐19: A qualitative phenomenological study

Abstract: Aim This study sought to describe the experiences of critical care nurses caring for patients infected by coronavirus disease 2019 (COVID‐19). Design A qualitative phenomenological design was used. Methods We enrolled 15 nurses who provided care for patients infected by COVID‐19 purposively and through snowballing, using a phenomenological approach in critical care units of Iran's public hospitals between May and June 2020. The semi‐structured interviews were carried out either via face‐to‐face or telephone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 39 publications
4
73
0
6
Order By: Relevance
“…The supply of gloves was reduced. Equipment was scarce” ( 34 ); “ As a nurse, you are in an important place. You are always in contact with the patient, but you are always in the background in the system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The supply of gloves was reduced. Equipment was scarce” ( 34 ); “ As a nurse, you are in an important place. You are always in contact with the patient, but you are always in the background in the system.…”
Section: Resultsmentioning
confidence: 99%
“…Nurses believe that they need care and support from other people outside, for example, their families and friends, which could be a great spiritual boost during tough times. “ I was inspired by the fact that my family was proud of me” ( 34 ). However, to the distress of some nurses, their families feared infection, and the lack of family support troubled the nurse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several qualitative studies have addressed experiences of the pandemic, exploring the perceptions of hospitalised patients [ 16 ], their family members [ 17 ], and frontline healthcare workers at hospitals [ 18 , 19 , 20 , 21 ]. However, we were unable to find studies that collected and comprehensively examined the perspectives of older persons living in nursing homes and long-term care facilities, employees of these facilities, or family members of residents during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of depression, anxiety, and stress is associated with worse patient care safety and health care quality [ 14 ], higher occurrence of adverse events [ 15 ]. On the other hand, the COVID-19 pandemic has an important role in the well-being of healthcare professionals, especially nurses [ 16 ]. A systematic review and meta-analysis showed that almost one-third of nurses had depression, anxiety, and stress during the COVID-19 pandemic [ 17 ].…”
Section: Introductionmentioning
confidence: 99%